2020
DOI: 10.2147/amep.s233368
|View full text |Cite
|
Sign up to set email alerts
|

<p>Health Professionals’ Readiness and Its Associated Factors to Implement Electronic Medical Record System in Four Selected Primary Hospitals in Ethiopia</p>

Abstract: Background: Incorporating electronic medical record systems (EMRs) into the healthcare system is not only about modernizing the health system, but is about saving lives by facilitating communication and practicing evidence-based decision. Globally, more than 50% of EMR projects fail before they reach their target. Even though EMRs are an essential tool for health care, their adoption and utilization remains low in developing countries including Ethiopia. Objective: The aim of this study was to determine health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 12 publications
8
42
5
1
Order By: Relevance
“…2,3 Health technology applications, like hospital information system (HIS), electronic health record (EHR), mobile health (M-health), decision support system (DSS), electronic medical record system (EMR) and research/data collection systems (RCS) have a big value in different settings of the healthcare by reducing healthcare costs, advancing access for up-to-date information, enable quick access for patient records and improve communication between patient and healthcare providers. [4][5][6][7] Over the past decade, the practical implementation and integration of eHealth systems have been scaled drastically. Many developed nations are utilizing eHealth technologies and make a real difference in improving patient care, and the provision of efficient and effective healthcare services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Health technology applications, like hospital information system (HIS), electronic health record (EHR), mobile health (M-health), decision support system (DSS), electronic medical record system (EMR) and research/data collection systems (RCS) have a big value in different settings of the healthcare by reducing healthcare costs, advancing access for up-to-date information, enable quick access for patient records and improve communication between patient and healthcare providers. [4][5][6][7] Over the past decade, the practical implementation and integration of eHealth systems have been scaled drastically. Many developed nations are utilizing eHealth technologies and make a real difference in improving patient care, and the provision of efficient and effective healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…2 , 3 Health technology applications, like hospital information system (HIS), electronic health record (EHR), mobile health (M-health), decision support system (DSS), electronic medical record system (EMR) and research/data collection systems (RCS) have a big value in different settings of the healthcare by reducing healthcare costs, advancing access for up-to-date information, enable quick access for patient records and improve communication between patient and healthcare providers. 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Ethiopia, Kuwait and Nigeria reported similar findings though slight variations existed in the methodology of assessment used. 19 , 20 , 22 , 23…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of healthcare professionals were either not ready 75,82,78 or not willing 72,81 to use EHR. Some healthcare professionals still preferred paper-based records to EHR in their daily work 74,77,79,80,81 while other preferred EHR.…”
Section: Digital Health Technologiesmentioning
confidence: 99%
“…76 Lack of access to EHR training, computer skills, and performance expectancy were the major barriers to their willingness or intention to use EHR. 71,72,73,74,75,77,78,81,82…”
Section: Digital Health Technologiesmentioning
confidence: 99%